2008
DOI: 10.3174/ajnr.a1098
|View full text |Cite
|
Sign up to set email alerts
|

Retreatment of Previously Embolized Cerebral Aneurysms: The Risk of Further Coil Embolization Does Not Negate the Advantage of the Initial Embolization

Abstract: BACKGROUND AND PURPOSE: A significant minority of aneurysms treated by endovascular means undergo additional subsequent therapy to treat aneurysm recurrence. Our study was undertaken to determine the risk of additional coil embolization of aneurysms recurring following endovascular therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(48 citation statements)
references
References 15 publications
4
43
0
1
Order By: Relevance
“…Smaller remnants are typically not treated, whereas larger remnants may prompt additional therapies, either repeat coiling or surgical clipping. 3,21 When the performance of MRA in detecting these larger and thus clinically more worrisome aneurysm remnants was evaluated, sensitivities diminished; this change is largely explained by MRA misclassification of class 3 aneurysm remnants as class 2. However, CE-MRA at both field strengths had greater sensitivity (ie, less underclassification) for these larger (class 3 or 4) aneurysm remnants than TOF-MRA at 1.5T.…”
Section: Discussionmentioning
confidence: 99%
“…Smaller remnants are typically not treated, whereas larger remnants may prompt additional therapies, either repeat coiling or surgical clipping. 3,21 When the performance of MRA in detecting these larger and thus clinically more worrisome aneurysm remnants was evaluated, sensitivities diminished; this change is largely explained by MRA misclassification of class 3 aneurysm remnants as class 2. However, CE-MRA at both field strengths had greater sensitivity (ie, less underclassification) for these larger (class 3 or 4) aneurysm remnants than TOF-MRA at 1.5T.…”
Section: Discussionmentioning
confidence: 99%
“…44 These outcomes are per procedure, and the risk per patient would increase in cases of retreatment, the latter being negligible after clipping. Renowden et al 47 reported that 6% of 1631 patients required retreatment after coiling of 1834 mostly ruptured aneurysms. They found a lower morbidity in retreatment coiling procedures compared with the initial procedure: 3 cases of thromboembolism from 99 recoiling procedures.…”
Section: Efficacy and Safetymentioning
confidence: 99%
“…In our series, no adverse events were shown on follow-up angiograms or occurred during retreatment with detachable coils. Recently, Renowden et al 42 and Henkes et al 43 reported complication rates of 2% to 3% in their large series of retreatment of previously embolized aneurysms. Followup procedures can be done safely, and the risk from retreatment with detachable coils does not negate the advantages of initial use of coil embolization.…”
Section: Aneurysm Recanalizationmentioning
confidence: 99%